Resiliência à pobreza multidimensional dos municípios do Centro-Oeste brasileiro - Barbosa, Francis Régis Gonçalves Mendes (2023)
One of the central criticisms of resilience approaches stems from the absence of a grounded theoretical framework amid an infinite number of concepts and meanings of the term. This gap creates difficulties in measuring, managing, and formulating public policies. To subsidize scientific advancement in this gap, this research proposed a theoretical-methodological framework to analyze and explain the determinants of multidimensional poverty resilience in the municipalities of Central-Western Brazil between 2013 and 2019. The theoretical model of Regional Resilience to Multidimensional Poverty (RRPM, acronym in Portuguese) was developed, whose determinants were: structural inequalities, productive structure, location, policy interventions, adverse shocks, and initial condition of vulnerability to poverty, in its dimensions. Methodologically, the Multidimensional Poverty Vulnerability Index (IVPM, acronym in Portuguese) was estimated for 2013-2019, using 14 indicators of tangible and intangible assets, basic capabilities, and demographics, whose absolute variation supported the construction of a binary variable proxy for resilience to multidimensional poverty. Exploratory Analysis of Spatial Data (AEDE, acronym in Portuguese) was employed in assessing the formation of Poverty Resilience (RPob, acronym in Portuguese) clusters. Subsequently, the odds of multidimensional poverty resilience (MPR) were estimated, given a set of 19 proxy explanatory variables for the determinants of regional multidimensional poverty resilience. The main results pointed to the formation of RPob clusters, heterogeneously distributed spatially and across federal units. The estimates attested that: i) the chances of RPM of the municipality positively influenced those of the neighbors and were influenced by them; ii) productive specialization, the Bolsa Família Program, the Community Health Agents, and adverse shocks in the Municipalities Participation Fund increased the chances of RPM of the municipalities, a result that extended to the neighbors in the case of medium technological intensity jobs. On the other hand, bordering the North-Northeast regions of Brazil and adverse shocks in the proportion of Individual Microentrepreneurs (MEIs, acronym in Portuguese) reduced the chances of RPM, with spatial spillovers in the predominantly rural profile; iii) the average of the 2013 IVPM for the 19 neighbors reduced the municipality's chances of RPM, however, not applicable to the overall effects of the initial IVPM. The main contributions are grounded in the proposition of the theoretical-methodological framework of RRPM and the set of theoretical and empirical results that accepted the research hypotheses that resilience and vulnerability to multidimensional poverty are distinct and not necessarily opposing elements in the context of the Midwest of Brazil.